Colorectal Cancer associated with pediatric inflammatory bowel disease: a case series - Min Jee Kim (BMC, 2021)
Abstract Background Inflammatory bowel disease (IBD) is associated with an increased risk of Colorectal cancer (CRC), and its most important risk factors are the duration and extent of the disease. Pediatric-onset inflammatory bowel disease has a tendency for a more extensive, more severe, and longer predicted disease duration than adult-onset inflammatory bowel disease. This study aimed to identify the clinical characteristics of patients with CRC related to pediatric-onset IBD and consider the appropriateness of current surveillance endoscopy recommendations for the detection of premalignant lesions and early-stage CRC. Methods We searched a research platform based on the SUPREME electronic medical record data-mining system to identify cases of colorectal malignancy in patients with pediatric IBD that presented between 2000 and 2020. Results During the follow-up, 4 (1.29 per 1000 person years) out of 443 patients with PIBD was diagnosed with CRC. The median age at diagnosis of CRC was 18.5 (range: 15–24) years, and the median period from diagnosis of IBD to CRC was 9.42 (range: 0.44–11.96) years. The sigmoid colon was the most frequent location of CRC (in 3 of the 4 cases). Adenocarcinoma was the most common histological type (in 2 of the 4 cases). Conclusions Patients with pediatric-onset IBD exhibited a much shorter disease duration than that of adult-onset IBD at the time of diagnosis of CRC, suggesting that surveillance endoscopy for the detection of precancerous lesions and early-stage cancer should be initiated earlier in pediatric patients than in adult patients.